2005
DOI: 10.1111/j.1744-7402.2005.02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel CO2 Absorbents Using Lithium‐Containing Oxide

Abstract: We have discovered a series of lithium‐containing oxides that immediately react with ambient carbon dioxide (CO2) up to 700°C. The products react and return reversibly to the oxides at a temperatures higher than about 700°C. The absorption capacity surpasses that of other CO2 absorbents by a factor of 10. Utilizing these absorbents, the possibility of a CO2 separation system that operates at around 500°C is proposed. It is generally believed that a CO2 separation process operable at temperatures higher than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 27 publications
3
95
0
2
Order By: Relevance
“…The lithium silicate showed good capturing capacity for the CO 2 at pre-combustion temperature conditions. The observed results of capturing capacity of lithium silicate for the CO 2 are also supported by the reported values in the literature 1) [6][7][8][9][10][11][12][13][14]. In lithium silicate, lithium plays an important role in capturing the CO 2 by forming lithium carbonate and then its decomposition in the presence of silica at high temperature.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The lithium silicate showed good capturing capacity for the CO 2 at pre-combustion temperature conditions. The observed results of capturing capacity of lithium silicate for the CO 2 are also supported by the reported values in the literature 1) [6][7][8][9][10][11][12][13][14]. In lithium silicate, lithium plays an important role in capturing the CO 2 by forming lithium carbonate and then its decomposition in the presence of silica at high temperature.…”
Section: Resultssupporting
confidence: 93%
“…Aluminum and iron doped in lithium silicate have been explored for capturing carbon dioxide from flue gases. Lithium silicate has been demonstrated as an excellent adsorbent for the capture of carbon dioxide [10][11][12][13]. The hydrotalcite containing calcium or magnesium and aluminum are good adsorbents for capturing carbon dioxide in the temperature range 100°C-500°C.…”
Section: Introductionmentioning
confidence: 99%
“…Several adsorbents have been proposed for CO 2 capture, including carbon fiber monolithic adsorbents [34], activated carbon fiber-phenolic resin composites [35], melamine-formaldehyde highly porous adsorbents [36], amine immobilized adsorbents [37], red mud [38], steam-activated anthracite [39], activated carbon [40], lithium zirconate [41], lithium silicate [42,43], alumina, metallic oxides and zeolites [44] among others [45,46]. Sjostrom and Krutka [47] compared several adsorbents and concluded that carbon-based materials present excellent stability, while zeolites work well under dry conditions.…”
Section: Adsorptionmentioning
confidence: 99%
“…Li 2 ZrO 3 synthetic sorbents are also reported in literature with better multicycle stability, but the costs are prohibitive. 79,82 Kusakabe et al 83 proposed selective CO oxidation membrane concept to facilitate SMR reaction. Yttria -stabilized zirconia (YSZ) membrane was deposited on the surface of a porous alumina support tube by sol -gel procedure.…”
Section: Reactor Design and Developmentmentioning
confidence: 99%